Analisis dampak Pembangunan Infrastruktur Dasar terhadap Kehidupan Sosial Masyarakat Perabaga Distrik Piramid Kabupaten Jayawijaya - Evelyne Afredytha Wenda; Lazarus Ramandei; Sudiro Sudiro (Fakultas Teknik Universitas Cenderawasih, 2024)
This research examines the impact of infrastructure development on people's lives in Kampung Perabaga, Piramid District, Jayawijaya Regency, Papua. Against the background of the increasing need for adequate infrastructure, this study aims to evaluate positive and negative impacts arising from the development of basic infrastructure such as roads, bridges, drainage, telecommunications, and roads. such as roads, bridges, drainage, telecommunications, and clean water in the region. region. The study used qualitative methods through observation, interviews, and documentation to obtain in-depth data on the condition of the infrastructure and its infrastructure and its influence on the economic, social, and welfare of the local community. of the local community. The results show that, although the development of basic infrastructure development has had a positive impact on economic activity and social interaction in the community, there are still significant shortcomings in the social interaction of the community, there are still significant shortcomings in drainage, telecommunication networks, and adequate access to clean water. Based on these results, the research recommends further planning and evaluation so that infrastructure development in Perabaga Village can run effectively and sustainably, according to the needs of the community. effective and sustainable, in accordance with the needs of the local community.